Precise pathogen detection and clinical characterization of bronchiectasis - Gao, Qinghua; Xu, Jiahao; Ma, Yue; Zhou, Siji; Zhang, Lei; Chen, Liping; Yi, Yongning; Hou, Ting; Zhang, Qiaoli; He, Jian (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThis study aims to evaluate the utility of molecular diagnostic techniques in identifying pathogens in bronchiectasis and to investigate the differences in clinical characteristics and pathogen distribution among patients with different microbial infections.MethodsThis retrospective study collected and analyzed clinical data and lower respiratory tract pathogen detection results from 410 patients with bronchiectasis admitted to the Anning First People’s Hospital Affiliated to Kunming University of Science and Technology, between August 2020 and August 2024. By comparing molecular diagnostic methods with conventional culture, we assessed differences in pathogen detection rates and spectrum, evaluated the diagnostic performance of molecular techniques relative to traditional methodologies, and analyzed the clinical characteristics of bronchiectasis patients with different microbiological etiologies.ResultsCompared with conventional microbiological testing (CMT), molecular diagnostics demonstrated significantly higher sensitivity, positive predictive value, and negative predictive value. The most frequently detected bacteria were Haemophilus influenzae (26.83%), Pseudomonas aeruginosa (14.88%), Streptococcus pneumoniae (13.17%), Klebsiella pneumoniae (9.02%), and Staphylococcus aureus (4.39%). Patients infected with P. aeruginosa had significantly lower body mass index (BMI) compared to those infected with H. influenzae, as well as more severe lung function impairment. Inflammatory markers, including white blood cell (WBC) count and C-reactive protein (CRP), were significantly higher in the P. aeruginosa group than in the H. influenzae group. In terms of pathogen detection, the conventional culture positivity rate was significantly higher in the P. aeruginosa group compared to the H. influenzae group, whereas the false-negative rate of culture was markedly higher in the H. influenzae group. Molecular diagnostics showed high true-positive rates in both groups, though slightly lower in the P. aeruginosa group than in the H. influenzae group. Furthermore, patients infected with P. aeruginosa had significantly higher rates of respiratory failure, cystic bronchiectasis, and oxygen therapy requirement compared to those infected with H. influenzae.ConclusionThe application of molecular diagnostic technology has significantly improved the detection rate of pathogens in patients with bronchiectasis, especially for fastidious bacteria and rare pathogens. This method can provide a more comprehensive understanding of the distribution of microorganisms and disease characteristics, shorten the diagnosis cycle, accurately guide anti-infection treatment decisions and assist in prognosis assessment.